ZARDUSHTIYLIK BILAN BOG‘LIQ IBODAT MAROSIMLARNING AVESTODA AKS ETISHI - Xaitov Nazirbek, Abdurasulov Xurshid (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
In this article, the Holy Book of Zoroastrianism, ―Avesto", as well as the comments on the education advanced in it, their introduction to the youth of the present time, were discussed.